Tracing Pathways 雲路 Interdisciplinary Studies on Modern and Contemporary East Asia - CUCINELLI, Diego; Scibetta, Andrea (Studi e saggi, 2020)
This volume collects contributions written by eight authors interested in different research areas in East Asian Studies. Divided into a Japanese and a Chinese section, it explores topics ranging from East Asian literatures to contact linguistics and sociology. The Japanese section contains four essays about contemporary Japanese cinema and different aspects of Japanese modern and contemporary literature (i.e. the literary motif of kame naku, 'crying turtle', yuri manga, and tenkō bungaku, the 'literature of conversion'). The Chinese section concerns two main macro-topics: on the one hand, it focuses on issues related to cultural contacts between Italy and China; on the other hand, it deals with Chinese migration to Italy, highlighting socio-historical aspects and cultural production.